Adevonin, a novel synthetic antimicrobial peptide designed from the Adenanthera pavonina trypsin inhibitor (ApTI) sequence. (17th November 2018) - Rodrigues, Mayara S.; Oliveira, Caio F. R. de; Almeida, Luís H. O.; Neto, Simone M.; Boleti, Ana Paula A.; Santos, Edson L. dos; Cardoso, Marlon H.; Ribeiro, Suzana M.; Franco, Octávio L.; Rodrigues, Fernando S.; Macedo, Alexandre J.; Brust, Flávia R.; et al.
ABSTRACT: The biological activities and the structural arrangement of adevonin, a novel antimicrobial peptide, were investigated. The trypsin inhibitor ApTI, isolated from Adenanthera pavonina seeds, was used as a template for screening 18-amino acid peptides with predicted antimicrobial activity. Adevonin presented antimicrobial activity and minimum inhibitory concentrations (MIC) ranging from 1.86 to 7.35 µM against both Gram-positive and – negative bacterial strains. Moreover, adevonin exerted time-kill effects within 10 min and both susceptible and drug-resistant bacterial strains were affected by the peptide. In vitro and in vivo assays showed that, at MIC concentration, adevonin did not affect human fibroblasts (MRC-5) viability or Galleria mellonella survival, respectively. Hemolytic activity was observed only at high peptide concentrations. Additionally, nucleic acid efflux assays, gentian violet uptake and time-kill kinetics indicate that the antimicrobial activity of adevonin may be mediated by bacterial membrane damage. Furthermore, molecular dynamic simulation in the presence of SDS micelles and anionic membrane bilayers showed that adevonin acquired a stable α-helix secondary structure. Further studies are encouraged to better understand the mechanism of action of adevonin, as well as to investigate the anti-infective activity of this peptide.